Organizational Culture and Its Effect on Employee Motivation - Siddiqi, Khowaja Abdul Jawad; Jamal, Ahmad Zamir (Journal for Research in Applied Sciences and Biotechnology, 2024)
Organizational culture plays a critical role in addressing these demands by maintaining the stability of the social system within the organization and minimizing individual differences. It fosters a sense of identity and belonging among employees, which is directly related to employee turnover and workplace harmony. The primary objective of this research is to examine the impact of organizational culture on employee motivation. Sub-objectives include assessing the impact of organizational culture on employee retention and organizational performance. The main research questions are: How does organizational culture affect employee motivation? How does it influence employee retention? And how does it impact organizational performance? Corresponding hypotheses posit that organizational culture positively affects employee motivation, retention, and organizational performance. For this study, data were collected using both primary and secondary methods. Primary data were gathered through a 30-question questionnaire distributed to 30 employees at Jahan University, while secondary data were sourced from relevant journals, books, and websites. The aim of this research is to elucidate the effects of organizational culture on employee motivation.